STRESS AMONG EARLY ADOLESCENTS AND MATERNAL AND TEACHERS ROLE PERCEPTION IN ADDRESSING ADOLESCENTS' STRESS IN SELECTED SCHOOLS OF THIRUVANANTHAPURAM - Aswathy K L; Kasturi R A AND Maxie A (Nitte University Journal of Health Science, 2015)
Objective: The objectives of the study were to assess the stress of early adolescents and to describe the role perceptions of mothers and teachers in addressing adolescent stress. Materials and Methods: This quantitative descriptive survey was conducted in two phases in Thiruvananthapuram district, Kerala. Data were collected from early adolescent children (959), their teachers (61) and mothers (136). In the first phase, level of stress and source of stress among early adolescent children and teachers' role perception in addressing adolescent stress were measured. In the second phase, role perception in addressing their adolescent's stress was assessed among mothers of adolescents with high stress. Result: A total of 97 (10.1%) adolescents had severe stress. Majority of adolescents have cited mothers' and fathers' parenting role as their major stressor (56.5% and 53.5% respectively). Mothers reported that over watching of television is a major cause of lack of interest in studies and that is the main reason for stress at home. 37.7% of the teachers felt that school is giving a lot of academic stress to the child. Conclusion: The study finding calls for collective actions of student-teacher-parent associations to reduce stress of adolescents.